6
$\begingroup$

If $\sqrt{1-x^2}+\sqrt{1-y^2}=a(x-y)$, prove that $\frac{dy}{dx}=\sqrt{\frac{1-y^2}{1-x^2}}$

My Attempt $$ \frac{-2x}{2\sqrt{1-x^2}}-\frac{2y}{2\sqrt{1-y^2}}.\frac{dy}{dx}=a-a\frac{dy}{dx}\\ \implies \frac{dy}{dx}\bigg[a-\frac{y}{\sqrt{1-y^2}}\bigg]=a+\frac{x}{\sqrt{1-x^2}}\\ \frac{dy}{dx}=\frac{a\sqrt{1-x^2}+x}{\sqrt{1-x^2}}.\frac{\sqrt{1-y^2}}{a\sqrt{1-y^2}+x}=\sqrt{\frac{1-y^2}{1-x^2}}.\frac{a\sqrt{1-x^2}+x}{a\sqrt{1-y^2}-y} $$

How do I poceed further and find the derivative ?

$\endgroup$
  • $\begingroup$ you can eliminate $a$ with your first equation! $\endgroup$ – Dr. Sonnhard Graubner Apr 5 '18 at 10:26
4
$\begingroup$

After my comment you will get $$a\sqrt{1-x^2}+x=\frac{1-xy+\sqrt{1-x^2}\sqrt{1-y^2}}{x-y}$$ and $$a\sqrt{1-y^2}-y=\frac{1-xy+\sqrt{1-x^2}\sqrt{1-y^2}}{x-y}$$ and you will get the desired result!

$\endgroup$
  • $\begingroup$ How did you find this! I liked both your and JJ's answer, but how you found this? $\endgroup$ – King Tut Apr 5 '18 at 10:45
  • $\begingroup$ Hm, intuition and the result containes no $a$, these are the reasons $\endgroup$ – Dr. Sonnhard Graubner Apr 5 '18 at 10:51
5
$\begingroup$

Both $x,y\in[-1,1]$. So, $x=\sin\theta$ and $y=\sin\phi$ for some $\displaystyle \theta,\phi\in\left[\frac{-\pi}{2},\frac{\pi}{2}\right]$. Note that $\cos\theta, \cos\phi\ge0$.

We have $$\cos\theta+\cos\phi=a(\sin\theta-\sin\phi)$$

So, $$2\cos\frac{\theta+\phi}{2}\cos\frac{\theta-\phi}{2}=2a\cos\frac{\theta+\phi}{2}\sin\frac{\theta-\phi}{2}$$

$\displaystyle \tan\frac{\theta-\phi}{2}=\frac{1}{a}$ is a constant. So, $\displaystyle \frac{d\phi}{d\theta}=1$.

$$\frac{dy}{dx}=\frac{\cos\phi}{\cos\theta}\frac{d\phi}{d\theta}=\frac{\sqrt{1-y^2}}{\sqrt{1-x^2}}$$

$\endgroup$
  • $\begingroup$ you beat me to it ! +1 $\endgroup$ – David Quinn Apr 5 '18 at 10:49
  • $\begingroup$ Good answer but how can we say $y\in [0,1]$? $y\in [-1,0]$ according to plot for positive $a$ $\endgroup$ – King Tut Apr 5 '18 at 10:56
  • $\begingroup$ @$y\in[-1,1]$. But $\cos\phi=\sqrt{1-y^2}\in[0,1]$. This is true as $\phi \in[\frac{-\pi}{2},\frac{\pi}{2}]$. $\endgroup$ – CY Aries Apr 5 '18 at 11:25
  • $\begingroup$ I have a typo here. Will edit it $\endgroup$ – CY Aries Apr 5 '18 at 11:32
3
$\begingroup$

HINT : There is no parameter $a$ in the formula to be proved. So, first transform the initial equation into an equation where $a$ will be immediately eliminated by differentiation: $$\frac{\sqrt{1-x^2}+\sqrt{1-y^2}}{x-y}=a$$ Differentiate and simplify.

$\endgroup$
  • $\begingroup$ @KingTut just do the differentiation from the form of the equation stated by@JJacquelin u'll get the final answer. So my original post is certainly not incorrect. $\endgroup$ – ss1729 Apr 5 '18 at 10:39
  • $\begingroup$ @ss ok let me check the error. thanks! $\endgroup$ – King Tut Apr 5 '18 at 10:40
1
$\begingroup$

Move $a(x-y)$ to the LHS to make $F(x,y)=0$. Then: $$\frac{dy}{dx}=-\frac{F'_x}{F'_y}=-\frac{-\frac{x}{\sqrt{1-x^2}}-a}{-\frac{y}{\sqrt{1-y^2}}+a}=\frac{a\sqrt{1-x^2}+x}{a\sqrt{1-y^2}-y}\cdot \frac{\sqrt{1-y^2}}{\sqrt{1-x^2}}=\frac{\sqrt{1-y^2}}{\sqrt{1-x^2}},$$ because: $$\begin{align}&\frac{a\sqrt{1-x^2}+x}{a\sqrt{1-y^2}-y}= \\ &1 \iff a(\sqrt{1-x^2}-\sqrt{1-y^2})=-(x+y) \iff a(y^2-x^2)= \\ &-(x+y)(\sqrt{1-x^2}+\sqrt{1-y^2}) \iff a(x-y)=\\ &\sqrt{1-x^2}+\sqrt{1-y^2}.\end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.